Target cost management in practice : the supplier’s perspective - Afonso, Paulo (2010)
Target Cost Management (TCM) include target costing as well as other techniques inspired in Japanese cost management practices such as kaizen cost management and inter-organisational cost management practices (Kato, 1993; Cooper and Slagmulder, 1999, 2004). These techniques are important concepts and tools for managing product costs during the design stage (Kato, 1993; Ewert and Ernst, 1999) and to guide effective New Product Development (NPD) processes across the entire supply chain. Thus, based on a case study and drawing upon empirical evidence relating to the adoption and use of TCM practices in a supplier belonging to a global supply chain in the automotive industry, this work offers empirical evidence on TCM in practice. It was found that in suppliers, KC and further IOCM practices guide the development of (internal) TC procedures, i.e. the inverse situation when we are from the client’s perspective. Furthermore, this case study shows how the application of these techniques and the firm’s NPD process evolves and change together. It was found that the different TCM practices can be all important to increase the effectiveness of NPD processes and that the application of TCM evolves in time and that NPD processes influence the use and development of TCM in practice.